Superstition, atheism and reasonable faith in Acts 26: a Graeco-Roman perspective on Paul's defence before Festus and Agrippa - Germiquet, Edouard Ariste (Rhodes University, Faculty of Divinity, Department of Divinity, 2001)
This thesis investigates Luke"Ÿs presentation of Paul"Ÿs final and climactic defence of the gospel which takes place before Festus and King Agrippa II (Ac.26). It indicates how Luke has made use of the philosophical doctrine of the mean in order to present Christianity as a reasonable and rational faith. This investigation explores how Luke creates a literary framework within which to promote Paul as reasonable and rational through the application of the topos that true piety is the mean between the two extremes of superstition and atheism. The thesis is therefore structured around three dominant sections in which the major themes of superstition, atheism and rational faith are treated independently. Each section consists of an analysis of Luke"Ÿs choice of words and his description of the behavioural patterns of each representative group so that a consistent picture progressively emerges in support of the basic framework. At all stages of the investigation, reference is made to contemporary moral philosophers, Hellenistic Judaism and the early Christian apologists so that the language, literary settings and stereotypes used by Luke can be clearly defined. This not only clarifies the text of Acts 26 but contributes to an overall appreciation of Luke"Ÿs literary technique. At all points in the development of the thesis, the relevance and centrality which the resurrection has for Luke is kept in mind. This not only acts as a backdrop in understanding Luke"Ÿs depiction of the superstitious and the atheist but is crucial in grasping Luke"Ÿs presentation of Christianity as a rational faith. The thesis is brought to a close by a discussion on Luke's intended audience and the significance of his dedication to Theophilus.
Keywords: Uncatalogued